Reconstruction of Islamic Education Management through Strengthening the Integration of Islamic Values - Roudoh, Roudoh; Hidayati, Suci; Faidah, Nur; Susanti, Danis (Halaqa: Islamic Education Journal, 2024)
In the Islamic perspective, education management science has established Islamic principles and values that can guide teachers and students in achieving educational goals. The science of education management in particular does not contained meanings that are relevant to Islamic principles and values. In this increasingly modern era, it is necessary to study in depth how the science of educational management can guide teachers and students to behave and behave well and correctly, especially in the institution of Islamic education. The purpose and focus of this research is to analyze how the reconstruction of Islamic Education management can be aligned with the principles and values of Islam today through productivity, competence, welfare, effectiveness, morals, skills and loyalty. The method of use is the literature study (library reeseearch). The results obtained from the analysis show that Islamic education management can be reconstructed as an effort to improve the competence of human resources by focusing on all activities and management of institutional components that prioritize ethical excellence and strengthening the integration of Islamic values in the education process in Islamic educational institutions.